Apparent thermal acclimation of soil heterotrophic respiration mainly mediated by substrate availability. Issue 4 (20th November 2022) - He, Yanghui; Zhou, Xuhui; Jia, Zhen; Zhou, Lingyan; Chen, Hongyang; Liu, Ruiqiang; Du, Zhenggang; Zhou, Guiyao; Shao, Junjiong; Ding, Junxia; Chen, Kelong; Hartley, Iain P.
Abstract: Multiple lines of existing evidence suggest that increasing CO2 emission from soils in response to rising temperature could accelerate global warming. However, in experimental studies, the initial positive response of soil heterotrophic respiration ( R H ) to warming often weakens over time (referred to apparent thermal acclimation). If the decreased R H is driven by thermal adaptation of soil microbial community, the potential for soil carbon (C) losses would be reduced substantially. In the meanwhile, the response could equally be caused by substrate depletion, and would then reflect the gradual loss of soil C. To address uncertainties regarding the causes of apparent thermal acclimation, we carried out sterilization and inoculation experiments using the soil samples from an alpine meadow with 6 years of warming and nitrogen (N) addition. We demonstrate that substrate depletion, rather than microbial adaptation, determined the response of R H to long‐term warming. Furthermore, N addition appeared to alleviate the apparent acclimation of R H to warming. Our study provides strong empirical support for substrate availability being the cause of the apparent acclimation of soil microbial respiration to temperature. Thus, these mechanistic insights could facilitate efforts of biogeochemical modeling to accurately project soil C stocks in the future climate. Abstract : We used a novel sterilization and microbial community inoculation approach to determine whether declines in respiration in alpine meadow soils exposed to 6 years of warming were caused by thermal adaptation or substrate depletion and identified a dominant role for substrate depletion. Our evidence that substrate depletion, and not microbial adaptation, cause the reduction in heterotrophic respiration in response to warming suggests that substantial amounts of C will be released as the world warms. It is thus critical that the C vulnerability of different stores is identified and reflected in the process‐based models that are used in future climate change projections.